The Effect of Self Assessment System, Tax Justice, and Trust in Tax Authorities on Tax Evasion - Andi Azra Indira Nur; Muhammad Iqbal (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
This study aims to analyze and prove the effect of the self-assessment system, tax justice, and trust in tax authorities on tax evasion on taxpayers registered at KPP Pratama Samarinda Ilir. This study used purposive sampling with a total sample that met the criteria of 100 respondents. The type of data used is quantitative data and the data source is a questionnaire. The analytical tool used in this research is smart pls 4.0. The results showed that the self-assessment system and trust in tax authorities have a significant and negative effect on tax evasion on corporate taxpayers registered at KPP Pratama Samarinda Ilir, and tax justice has no effect on tax evasion on corporate taxpayers registered at KPP Pratama Samarinda Ilir.